Extermism as one of the main threats to security of the Czech regions - Fuka, Jan; Horčička, Aleš (Univerzita Pardubice, 2009)
Area security ensuring belongs to the major activities undertaken by territorial authorities. Area security management includes legislative, administrative, economic, sociological and managerial elements, which are usually suitably mixed. Safety aspect within the strategic management at the level of territorial units at present - wrongly - is still quite underestimated, although it is necessary to understand that the provision of security in all circumstances must be one of the basic daily tasks for local governments. The aim of the article is to define the focus of safety management as an important real part of strategic management and strategic planning of territorial units, to identify the most important threats to the Czech regions in the early 21st century with emphasis on extremism.
Keywords: area security; safety management; Strategic Management; regions; microregions; threats; EXTREMISM; Terrorism